Nomadism vs. pastoralism in the interfluve of the Vistula and the Dnieper rivers four and three thousand years BC. Current trends in the discussion - Szmyt, Marzena; Kośko, Aleksander (Balcanica Posnaniensia. Acta et studia, 2007)
The authors address the issue of the relationship between nomadism and pastoralism in the Vistula-Dnieper interfluve in the 4th–3rd millennium BC, presenting the current state of research. The background for the analysis is the significance of this area as a borderland between Central Europe and the Pontic region, where cultural processes intersected and early models of animal husbandry-based economies were formed. The aim of the article is to critically analyse the concepts of ‘nomadism’ and ‘pastoralism’ and to attempt to capture the differences and points of contact between these categories in the context of the prehistory of Central and Eastern Europe. The research is based on an analysis of archaeological materials (including the iconography of funnel-shaped pottery, animal remains, elements of carts and harnesses), supplemented by archaeozoological interpretations and terminological and typological discussions in the light of the literature on the subject. The conclusions indicate that although favourable conditions for the development of mobile forms of animal husbandry existed in the 4th–3rd millennium BC, in Central Europe they were episodic in nature and most often associated with crisis situations.